Невідомі сторінки історії Центрального державного кінофотофоноархіву України імені Г.С. Пшеничного - Ємельянова, Т. (Архіви України, 2008)
The article is dedicated to the initial period of CSCPPAU history. Based on the historical sources complex analysis it examines formation and functioning peculiarities of this specialized archival institution. The article includes the structure, content and acquisition of audio and visual documents of the above archives. It also undertakes an analysis of archival documents preservation and control as well as reference apparatus development and use of archival information.